Solution mediated phase transformation (RHO to SOD) in porous Co-imidazolate based zeolitic frameworks with high water stability - Biswal, Bishnu P.; Panda, Tamas; Banerjee, Rahul (Chemical Communications, 2012)
Here we report a highly porous, water stable Co based ZIF [CoNIm (RHO)] and its solution mediated phase transformation to a less porous and water unstable ZIF [CoNIm (SOD)]. CoNIm (RHO) has high Langmuir surface area [2087 m(2) g(-1)] as well as high water adsorption [200 cm(3) (STP) g(-1)] capacity.